Belgravia : the next chapter [videorecording (DVD)] - Fellows, Julian; Edmundson, Helen, 1964- (Universal, 2024)
Belgravia, 1871. The eligible Lord Frederick Trenchard meets the bewitching Clara Dunn, and they fall deeply in love. A romantic courtship and proposal follow, and Clara is swept off her feet. But there are hidden depths to Frederick; he carries trauma from his childhood, following years of emotional neglect and resentment from his father, who favoured the younger son, James. Clara is highly perceptive, quickly realising there is trauma at the heart of Frederick's guarded manner. She grows convinced that by fixing Frederick's relationship with his estranged brother she can also restore his happiness. In the midst of her plans, she starts to develop an unlikely friendship with the charming Dr Ellerby and is drawn into his bohemian world. Excited by the passionate way they live, Clara begins to question her place in the world. Clara and Frederick must chart a course through the rumours which threaten them and confront long-buried secrets as they search for lasting happiness.